The high-rank syntaxa of the rock-cliff and scree vegetation of the mainland Greece and Crete - Mucina, Ladislav; Dimopoulos, P.; Sykora, K.; Georgiadis, T. (1997)
A revision was undertaken of the high-rank syntaxa of the vegetation occurring in rock fissures,ledges and screes of mainland Greece and Crete. All published phytosociological relev6s available were collected and subjected to numerical classification and ordination. Four orders (Androsacetalia vandelii, Onosmetalia frutescentis, Potentilletalia speciosae and Petromaruletalia pinnatae) comprising 8 alliances (one of them new) were distinguished within the Asplenietea trichomanis (rock fissures, clefts, and ledges). The scree vegetation was classified partly within the Thlaspietea rotundifolii (Drypidetalia spinosae with 2 alliances) and partly within the Daphno-Festucetea (Saturejo-Scutellarietalia - a new order, with 2 alliances). Ordination revealedclear differences in floristic composition of the alliances distinguished. The studied chasmophytic vegetation of Greece contains a very high proportion of endemics which serve as diagnostic species of the syntaxa. Further, an analysis of chorological species spectra suggested that the chorological homogeneity of a syntaxon should be considered an important diagnostic feature at high-syntaxon levels.